An analisis of tax planning implementation on the income tax agency - Cherya Trinanda Buchika (Enrichment : Journal of Management, 2023)
In this case, service and non-services companies as taxpayers are required to pay taxes. For companies, taxes are a source of expenditure (Cash Disbursement) without direct cash for the company. So, many companies usually make efforts to pay their taxes owed as small as possible . PT. Semesta Nusantara Konstruksi is a company engaged in the construction of building construction, income/profit obtained by PT. Semesta Nusantara Konstruksi automatically. The company has become a tax subject as well as a tax object of a country. PT. Semesta Nusantara Construction provides full tax returns to its employees. However, the method used by this company is the Net method. This research used quantitative research which was conducted at PT Semesta Nusantara Konstruksi. It is one of the companies engaged in the construction field. Data collection methods was through literature studies, interviews, observations, and documentation. Calculation of Income Tax article 21 on PT. Semesta Nusantara Konstruksi related to paying income tax till uses the calculation charged to the employer (Net). It shows that PT. Semesta Nusantara Konstruksi still needs to apply the Gross up method in determining tax allowances Calculation of Income Tax article 21 on PT. Semesta Nusantara Konstruksi related to paying income tax till uses the calculation charged to the employer (Net). It shows that PT. Semesta Nusantara Konstruksi still needs to apply the Gross up method in determining tax allowances.